Electrochemical studies of blend polymer electrolytes based on PVDF HFP/PEMA for Proton Battery / Siti Rudhziah Che Balian … [et al.] - Che Balian, Siti Rudhziah; Mat Fadzil, Aida Fazliza; Muhammad, Fadiatul Hasinah; Muda, Norhafiza; Mohamed, Nor Sabirin; Mohamed, Prof. Dr. Nor Sabirin (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Electrolytes system composed of PVDF- HFP, PEMA, NH4CF3SO3 and TIO2 have been prepared and characterized. The system containing 5 wt. %of TiO2 exhibited the highest room temperature conductivity of ~ 1.32 x 10 -3 S cm-1. This system was used as an electrolyte for the fabrication proton battery with the-configurations (Zn + ZnSO4.7H2O + C +PTFE)/PVDF-HFP/PEMA-NH4CF3SO3-(5 wt %) TiO2/ (MnO2 + C +PTFE) in order to investigate the performance of PVDF-HFP/ PEMA blend-based electrolytes in electrochemical ceils. The result shows that the proton battery discharged at higher load has the longest time of stable performance. This indicates that the electrolyte is more suitable for low current density battery application.